Мотивация как стимулирующий фактор в изучении иностранных языков взрослыми учащимися - Asta Balčiūnaitienė; Jovita Daukšytė; Larisa Voronova (Studia Ecologiae et Bioethicae)
Learning foreign languages is one of the most important skills intended for all adult learners and lasting all their lives. Because of the processes of globalization in the world, knowing foreign languages is perceived as being very valuable. Motivation can be described as an entity of external and internal factors that encourage a person to achieve certain goals. External motivation is influenced by a variety of external factors, i.e. a wish to get a better-paid job, a possibility to travel abroad, or success at an exam. Internal motivation is largely dependent on a person him/herself. It can be emotions caused by the process of learning or a desire to feel comfortable in multicultural surroundings. There are various factors that emerge when adults learn foreign languages: career, change of job or living place, family reasons, free-time and etc. In addition, every person should be encouraged to learn foreign languages and conditions must be met to achieve that. Dis paper presents a research carried out in 2012 by Vytautas Magnus University lecturers. Its aim was to determine the factors that motivate adult learners to study foreign languages in the extra-mural studies at Vytautas Magnus University as well as in English and Russian language courses for the general public at the university. For the research, 130 questionnaires were distributed among adult learners. In the questionnaires, the respondents were asked to indicate the motivating factors that make them learn foreign languages, their learning experiences, and difficulties. Afterward, the respondents were asked to indicate what skills and competencies they expect to acquire and if their expectations and needs for studying were met.